2017
DOI: 10.1267/ahc.17003
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen Accelerates Cell Proliferation through Estrogen Receptor α during Rat Liver Regeneration after Partial Hepatectomy

Abstract: Although estrogen is implicated in the regulation of cell growth and differentiation in many organs, the exact mechanism for liver regeneration is not completely understood. We investigated the effect of estrogen on liver regeneration in male and female Wistar rats after 70% partial hepatectomy (PHx) and performed immunohistochemistry, western blotting and Southwestern histochemistry. 17β-estradiol (E2) and ICI 182,780 were injected into male rats on the day before PHx. The proliferating cell nuclear antigen (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 44 publications
1
36
0
Order By: Relevance
“…After washing with 0.075% Brij L23 in PBS, sections were reacted with specific secondary antibody for 60 minutes. Then, sections were washed with 0.075% Brij L23 in PBS and counterstained with DAPI (Vector Laboratories, Burlingame, CA, USA) for 1 min [ 3 , 29 ]. Normal rat or goat IgG was used at the same concentration instead of the primary antibodies for each experiment as a negative control.…”
Section: Methodsmentioning
confidence: 99%
“…After washing with 0.075% Brij L23 in PBS, sections were reacted with specific secondary antibody for 60 minutes. Then, sections were washed with 0.075% Brij L23 in PBS and counterstained with DAPI (Vector Laboratories, Burlingame, CA, USA) for 1 min [ 3 , 29 ]. Normal rat or goat IgG was used at the same concentration instead of the primary antibodies for each experiment as a negative control.…”
Section: Methodsmentioning
confidence: 99%
“…The risk of TC as an SPM of breast cancer is significantly increased and vice versa, suggesting the effect of estrogen could not be neglected [ 16 ]. Estrogen could stimulate cell proliferation via ERα [ 17 , 18 ]. In human TC tissue, elevated expression of ERα has also been reported, especially when coexisting with breast cancer [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…The hepatic regenerative process in rats begins with an increase in the levels of various signaling molecules from the third hour after hepatectomy, peaks within 2-3 days, and ends at 5-7 days when the remnant lobe enlarges to the size of the original liver ( 18 ). In a similar study of rat liver regeneration after partial hepatectomy, it was shown that maximum liver regeneration at 36 and 48 h was significantly higher, even when only one drug dose (ICI 182,780) was administered 24 h before hepatectomy ( 19 ). In another rat study, orthotropic liver transplantation was performed after partial hepatectomy, with EGb761 intravenously administered 1 h prior to surgery, resulting in alleviation of hepatic inflammation/necrosis between 2 and 24 h postoperatively ( 20 ).…”
Section: Discussionmentioning
confidence: 99%